Teachers’ Understanding of Evidence of Students’ Social Emotional Learning and Self-Reported Gains of Monitored Implementation of SEL Toolkit - Martinsone, Baiba; Ferreira, Marco; Talić, Sanela (Journal of Education Culture and Society, 2020)
Aim. The aim of this study was to highlight and analyse teachers’ responses to the evidence of their students’ social emotional growth and teachers’ own gains from the monitored implementation of social emotional learning in their classes. Methods. The research group was composed of 312 teachers from Latvia and Slovenia, who were involved in the implementation of indirect social emotional learning through classroom instruction and formative assessment. A thematic analysis of the teachers’ written responses was performed. Results. A thematic analysis of the teachers’ responses indicated that initially they had mentioned mostly (expressed) general statements and only some small part of their responses included observable and measurable indicators of students’ social emotional skills improvement. Therefore, four months after the beginning of the intervention, teachers reported rather on their personal and professional gains from the participation in this intervention than provided general statements. Conclusions. The teachers’ improved self-reflection is a premise for them to consider evidence of students’ social emotional skills development thus facilitating purposeful social emotional learning in schools.